Uji Aktivitas Penghambatan Enzim Alfa Amilase Ekstrak Daun Kelor (Moringa Oleifera) - Putri Asih Mahalani; Kiki Mulkiya; Thyazen Abdo Hizam Al-Hakim (UNISBA Press, 2024)
Abstract. Diabetes mellitus (DM) is a metabolic disorder resulting from loss of tolerance to carbohydrates which is influenced by genetic and clinical factors. Efforts to treat DM include inhibiting α-amylase, a digestive enzyme that breaks down starch in food. Moringa leaves have been used practically in the field of medicine. In vivo and in vitro studies on the Moringa plant show its effectiveness in treating inflammation, hyperlipidemia, and hyperglycemia. Moringa has phytochemical properties including flavonoids and felnolic acid with inflammation-related, antioxidant, and antibacterial activities. This study aims to test the inhibitory activity of the alpha amylase enzyme and determine the total flavonoid content of Moringa leaf extract. The alpha amylase enzyme inhibitory activity test on Moringa leaves was carried out in vitro using the DNS (Dinitrosalicylic acid) method at concentrations of 10 ppm, 15 ppm, 20 ppm, 25 ppm and 30 ppm. The results obtained are expressed by the IC50 value of Moringa leaf extract, which is 26.25 ppm. The results of determining the total flavonoid content had a value of 114.702%. Abstrak. Diabetes melitus (DM) gangguan metabolisme akibat hilangnya toleransi terhadap karbohidrat, dipengaruhi oleh faktor genetik dan klinis. Upaya penanganan DM termasuk penghambatan α-amilase, enzim pencernaan yang memecah pati dalam makanan. Daun kellor sudah digunakan selcara praktis dalam bidang pelngobatan,. Pada studi in vivo dan in vitro pada tanaman kellor sudah melrelkomelndasikan elfelktivitasnya dalam melngobati pelradangan, hipelrlipidelmia, dan hipelrglikelmia. Kellor mimiliki sifat fitokimia selpelrti flavonoid dan asam felnolik delngan aktivitasnya telrkait inflamels, antioksidan dan antibaktelri. Penelitian ini bertujuan untuk melakukan pengujian aktivitas penghambatan enzim alfa amilase dan menetapkan kadar flavonoid total dari ekstrak daun kelor. Uji aktivitas penghambatan enzim alfa amilase daun kelor (Moringa oleifera) dilakukan secara in vitro dengan metode DNS (Dinitrosalicylic acid) pada konsentrasi 10 ppm, 15 ppm, 20 ppm, 25 ppm, dan 30 ppm. Hasil yang diperoleh dinyatakan sebagai nilai IC50 pada ekstrak daun kelor yaitu sebesar 26,25 ppm hasil penetapan kadar flavonoid total memiliki nilai sebesar 114,702%.